VOLATILITY DEPENDENCE STRUCTURE BETWEEN THE MEXICAN STOCK EXCHANGE AND THE WORLD CAPITAL MARKET - López Herrera, Francisco; Santillán Salgado, Roberto J.; Cruz Ake, Salvador (Investigación Económica, 2016)
This paper studies the integration of the Mexican Stock Exchange (MSE) into the World Capital Market (WCM). We detect a long-run equilibrium relationship, despite the effects of structural breaks associated to different financial crises during our period of analysis (1987-2012). The analytical approach begins with the estimation of a bivariate VECM in the mean, including several dummy variables that capture the main crisis episodes that took place during the estimation period. Next, we specify a VARMA-GARCH model with Dynamic Conditional Correlation, and, finally, we fit a Clayton copula to returns, conditional on two volatility regimes (low and high), in order to further understand the nature of their dependence structure.